2012
DOI: 10.7309/jmtm.18
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Mobile Health and Risk Reduction in Patients with Diabetes Mellitus: Challenge and Opportunity

Abstract: Purpose: To examine scientific evidence on the effectiveness of mobile phone technology in Diabetes Mellitus (DM) care management. Methods: A systematic review was conducted through literature searches from three electronic databases and was restricted to English-language articles published between January 2002 and March 2012. Studies that used mobile phone intervention and reported changes in diet, physical activity, and blood glucose and /or glycosylated hemoglobin (HbA1c) levels were retrieved. A meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Studies that used mobile phone intervention and reported changes in diet, physical activity, and blood glucose and/or HbA1c levels were retrieved. Overall, significant improvements were observed in blood glucose and/or HbA1c concentration, adherence to medication, healthy lifestyle, and self-efficacy ( 11 ). These studies took place in several countries including the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that used mobile phone intervention and reported changes in diet, physical activity, and blood glucose and/or HbA1c levels were retrieved. Overall, significant improvements were observed in blood glucose and/or HbA1c concentration, adherence to medication, healthy lifestyle, and self-efficacy ( 11 ). These studies took place in several countries including the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Personalized messaging is linked to greater retention of participants. 41 Although tailored messaging programs are more expensive to develop than targeted messaging, they can still be largely computer generated and so cost-effective and scalable. 53 …”
Section: Tailoring Ehealth Interventions For Latino Populationsmentioning
confidence: 99%
“…Previous reviews have described the impact of mobile technology -based interventions centered solely on diabetes management [18][19][20][21][22] and weight loss. [23][24][25] Other reviews have highlighted a diverse group of studies in order to explore the role of mobile technology in terms of health promotion/ chronic disease prevention and/or management.…”
mentioning
confidence: 99%